Public Sector Response to COVID-19 Pandemic in India: Challenges and Lessons Learned - Dar, Showkat Ahmad; Akther, Fatima (Universitas Muhammadiyah Sidoarjo, 2023)
The COVID-19 pandemic has significantly impacted the public sector in India, leading to a range of challenges that have required swift and effective responses. This abstract provides an overview of the challenges faced by the public sector in India in responding to the pandemic and the lessons learned from the experience. The challenges faced by the public sector in India have included a shortage of medical supplies, equipment and hospital beds, as well as limited testing capacity and inadequate health infrastructure. Additionally, India's large population and the spread of the virus in densely populated urban areas have created additional challenges. Despite these challenges, the public sector has responded with a range of measures, including the establishment of COVID-19 hospitals and quarantine facilities, the provision of financial assistance to those affected by the pandemic, and the development of innovative solutions such as telemedicine and online consultation services. The experience of the COVID-19 pandemic has also highlighted a range of lessons for the public sector in India. These include the need for greater investment in healthcare infrastructure, the importance of effective communication and coordination between different levels of government, and the need for proactive planning and preparation for future pandemics. Overall, the response of the public sector in India to the COVID-19 pandemic has been a complex and challenging process, but it has also provided important lessons and insights for the future.